2018
DOI: 10.1177/2167479518794505
|View full text |Cite
|
Sign up to set email alerts
|

(Broad)casting a Wider Net: Clocking Men and Women in the Primetime and Non-Primetime Coverage of the 2018 Winter Olympics

Abstract: This study analyzed the frequency with which the 2018 Pyeongchang Winter Olympic broadcasts featured men and women athletes. To understand these portrayals, all 557 hr and 15 min of National Broadcasting Company’s (NBC) 2018 Winter Olympic telecasts were recorded. This recorded content included the 62 hr and 30 min of NBC’s primetime program and, for the first time, all of the remaining non-NBC primetime coverage on NBC’s other networks. Women athletes received the majority of the clock time on the NBC primeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…A survey of scholarship suggests these in-house platforms are among the few spaces where gender balance occurs (B. D. Cooper & Cooper, 2009;Cunningham & Sagas, 2002;Cunningham et al, 2004). There are other instances where more balanced coverage has been observed, but they are often relegated to large international sporting events like the Olympics or the World Cup (Arth et al, 2019;A. Billings & Angelini, 2019;Petty & Pope, 2019;Sherwood et al, 2017;Wolter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A survey of scholarship suggests these in-house platforms are among the few spaces where gender balance occurs (B. D. Cooper & Cooper, 2009;Cunningham & Sagas, 2002;Cunningham et al, 2004). There are other instances where more balanced coverage has been observed, but they are often relegated to large international sporting events like the Olympics or the World Cup (Arth et al, 2019;A. Billings & Angelini, 2019;Petty & Pope, 2019;Sherwood et al, 2017;Wolter, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Olympic research found that female athletes were underrepresented in event coverage and framed along gender stereotypes (Angelini & Billings, 2010;Billings et al, 2009Billings et al, , 2013Dyreson, 1996;Hardin et al, 2004;Mishra, 2014). In recent years, researchers found that televised Olympic coverage is more balanced (Arth et al, 2019;Billings & Angelini, 2019;Sherwood et al, 2017). The purpose of the current study is to determine whether recent trends toward more balanced gender frames extend to the digital content produced and shared on the social media platforms (SMPs) of North American official Olympic broadcasters.…”
Section: Abstract Social Media Instagram Gender Olympics Framingmentioning
confidence: 99%
“…The clock time for men and women for the 2002–2018 Winter Games was starkly different in earlier years, with men at about 65% and women at about 35%, and has progressed to an almost even split, with women overtaking men in the 2018 coverage (Billings & Angelini, 2019). Percentages can vary with prime time versus nonprime time coverage, as female athletes received more prime time coverage (52.2%) but less nonprime time coverage (41.4%) than men in the 2018 Winter Olympic Games (Arth, Hou, Rush, & Angelini, 2018).…”
Section: Review Of Literaturementioning
confidence: 99%